Observational study on seizures of marijuana, cocaine, and crack in a city in the metropolitan region of Belo Horizonte, Brazil - Costa, Anna Carolina Moura; Freitas de Oliveira , Lara Luiza; França Figueredo Coelho , Júlia; Lorenna Souza Sales, Thaís; Homero Huertas dos Santos, Álvaro; Colén Fonseca, Beatriz; Paulina Silva Castro, Isabel; Jesus Marinho, Adriane; Sanches, Cristina; Drumond Chequer, Farah Maria (Revista Brasileira de Criminalística, 2023)
It is estimated that 275 million people in the world between 15 and 64 years old used drugs of abuse in 2020. In the same year, the Brazilian Federal Police seized about 546,439.57 kg of marijuana and 91,234.87 kg of cocaine, demonstrating how much these substances are present in everyday life. This study aimed to describes the epidemologic profile of seizures of marijuana, cocaine, and crack, carried out by the Civil Police, in city of Betim, Minas Gerais State, Brazil. This is a descriptive observational study, carried out on a documentary basis, in the years 2017 and 2018. The information was collected through the analysis of the final reports issued by the Betim Police Department, and the Social Defense Event Records (REDS). A total of 568 definitive reports and REDS were analyzed, and the sociodemographic profile of the individual apprehended in connection with illicit drugs is composed mainly of men (86.4%), single (86.6%), with incomplete elementary education (33.2%), with a median age of 20 years. The 24-hour Police Station (88%) and the north region Police Station (22.7%) were where the largest seizures took place; illicit drug trafficking (85.6%) was the main crime related to these seizures, and marijuana was the most seized drug (51.1%). Knowledge of the profile of drug seizures in this region allows for the creation of prevention measures for the trafficking and use of illicit drugs, contributing to the improvement of public health and safety.